CircMAP3K4 protects human lens epithelial cells from H2O2-induced dysfunction by targeting miR-193a-3p/PLCD3 axis in age-related cataract. Issue 3 (1st February 2023) - Ma, Yu; Liu, Yi; Shu, Baotong; Yang, Jianguo; Lv, Liang; Zhou, Lixiao; Wang, Lichun; Shi, Zongli
ABSTRACT: Circular RNAs (circRNAs) have shown pivotal regulatory roles in multiple human ocular diseases, including age-related cataract (ARC). Here, we explored the role of circRNA mitogen-activated protein kinase kinase kinase 4 (circMAP3K4, hsa_circ_0078619) in ARC pathology and its associated mechanism. The expression of RNAs and proteins was examined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot assay. Cell viability, senescence, proliferation, and apoptosis were analyzed by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, senescence-associated-β-galactosidase (SA-β-Gal) staining, 5-ethynyl-20-deoxyuridine (EdU) assay, and flow cytometry. The oxidative stress status of SRA01/04 cells was analyzed using the commercial kits. The interaction between microRNA-193a-3p (miR-193a-3p) and circMAP3K4 or phospholipase C delta 3 (PLCD3) was verified by dual-luciferase reporter assay, RNA immunoprecipitation (RIP) assay, and RNA-pull down assay. CircMAP3K4 was significantly down-regulated in ARC patients and H2 O2 -induced SRA01/04 cells. H2 O2 treatment restrained the viability and proliferation and promoted the senescence, apoptosis, and oxidative stress of SRA01/04 cells, and circMAP3K4 overexpression protected SRA01/04 cells from H2 O2 -induced dysfunction. MiR-193a-3p was a direct target of circMAP3K4, and circMAP3K4 overexpression-mediated protective effects in H2 O2 -induced SRA01/04 cells were largely reversed by the accumulation of miR-193a-3p. MiR-193a-3p interacted with the 3' untranslated region (3'UTR) of PLCD3, and PLCD3 knockdown largely overturned miR-193a-3p silencing-induced protective effects in H2 O2 -induced SRA01/04 cells. CircMAP3K4 up-regulated the expression of PLCD3 via sponging miR-193a-3p in SRA01/04 cells. In conclusion, circMAP3K4 protected SRA01/04 cells from H2 O2 -induced dysfunction in ARC through mediating miR-193a-3p/PLCD3 axis.